Methodological considerations for researching the financial costs of family caregiving within a palliative care context. Issue 4 (26th April 2016) - Gardiner, Clare; Allen, Ruth; Moeke-Maxwell, Tess; Robinson, Jackie; Gott, Merryn
Abstract : Background: The financial impact of family caregiving in a palliative care context has been identified as an issue which requires further research. However, little is known about how research should be conducted in this area. Objective: The aim of this study was to explore the opinions of family caregivers in New Zealand regarding the need to conduct research relating to the financial costs of family caregiving and to explore their perspectives on acceptable and feasible methods of data collection. Methods: A qualitative study design was adopted. Semistructured interviews were conducted with 30 family caregivers who were either currently caring for a person with palliative care needs or had done so in the past year. Results: All participants felt that research relating to the costs of family caregiving within a palliative care context was important. There was little consensus regarding the most appropriate methods of data collection and administration. Online methods were preferred by many participants, although face-to-face methods were particularly favoured by Ma¯ori participants. Both questionnaires and cost diaries were felt to have strengths and weaknesses. Conclusions: Prospective longitudinal designs are likely to be most appropriate for future research, in order to capture variations in costs over time. The lack of consensus for a single preferred method makes it difficult to formulate specific recommendations regarding methods of data collection; providing participants with options for methods of completion may therefore be appropriate.